Di(ver)sium: imágenes para coeducar - Dra. Carmen LÓPEZ-SAN SEGUNDO,Dra. Marina HERNÁNDEZ PRIETO,Dr. Alfredo GARCÍA PÉREZ OMAÑA (Fonseca, Journal of Communication, 2023)
Di(ver)sium is a teaching resource based on the use of photography and aimed at promoting the gender equality and affective-sexual diversity in secondary schools and higher education institutions. It optimizes the informative potential of ’Medianautas’ and ’Di(ver)sidades’,two actions aim at fostering the coeducation that develop at the University of Salamanca under the umbrella of the responsible research and innovation experience ’FotoC3: Citizenship, Creativity and Care’.